Differences in Students’ Attitudes on The Use of Information and Communication Technologies in Teaching According To the Type of Secondary School - Selma Porobić; Senada Mujić; Saima Omerašević; Marina Marković; Amina Saračević; Aziza Adb el Rahman; Fikreta Aljić; Belmina Tursunović (Društvene i Humanističke Studije)
The paper presents the results of a study aimed at examining whether there are differences in the attitudes of high school students about the importance of using information and communication technologies in teaching. The data were collected via a Google online survey, on a convinience sample of 312 high school students in Tuzla, of which 172 are students (those attending the Public Institution Secondary Medical School in Tuzla), while 140 are students (those attending the Public Institution Gymnasium “Meša Selimović” Tuzla). The results obtained indicate that high school students express a positive attitude towards the use of information and communication technologies in teaching, recognizing their usefulness in improving the quality of learning and the teaching process, with no difference between the two schools being established. However, the results indicate the existence of differences between high schools in terms of technical equipment, which may affect the possibility and manner of using information and communication technologies in teaching. This indicates the importance of further improving infrastructure conditions so that all students have equal opportunities to use information and communication technologies in learning. The above results offer a starting point for further research into factors that influence students’ attitudes towards the use of information and communication technologies in teaching.